A Longitudinal Analysis of the Relationship Between School Victimization and Student Mobility. (October 2013) - Carson, Dena C.; Esbensen, Finn-Aage; Taylor, Terrance J.
Schools have generally been viewed as "safe havens" from victimization experiences. Yet, there is no question that youth experience a variety of victimization while attending school. The current study expands research on victimization at school by focusing on mobile youth. School mobility is of concern to both educators and practitioners and is associated with a number of harmful as well as beneficial outcomes (e.g., dropout and school failure, deviant behaviors, or increased test scores and grades). This research uses longitudinal data from a sample of approximately 2, 000 youth to examine (1) the effect of in-school victimization on school mobility and (2) the consequences of school mobility on subsequent victimization. Findings from multilevel regression and change score analyses indicate that, in middle school, youth who are victimized are more likely to change schools and experience less victimization at the new school.